The art of racing in the rain ebook A novel. - Stein, Garth (2009)
NOW A MAJOR MOTION PICTURE FROM FOX 2000 STARRING MILO VENTIMIGLIA, AMANDA SEYFRIED, AND KEVIN COSTNER MEET THE DOG WHO WILL SHOW THE WORLD HOW TO BE HUMAN The New York Times bestselling novel from Garth Stein—a heart-wrenching but deeply funny and ultimately uplifting story of family, love, loyalty, and hope—a captivating look at the wonders and absurdities of human life . . . as only a dog could tell it. "Splendid." —People "The perfect book for anyone who knows that compassion isn't only for humans, and that the relationship between two souls who are meant for each other never really comes to an end. Every now and then I'm lucky enough to read a novel I can't stop thinking about: this is one of them." —Jodi Picoult "It's impossible not to love Enzo." —Minneapolis Star Tribune "This old soul of a dog has much to teach us about being human. I loved this book." —Sara Gruen